1976
DOI: 10.1037/0022-3514.33.4.460
|View full text |Cite
|
Sign up to set email alerts
|

The coronary-prone behavior pattern and the suppression of fatigue on a treadmill test.

Abstract: A study was conducted to test the hypothesis that Type A (coronary-prone) individuals would show greater suppression of subjective fatigue than Type B (non-coronary-prone) individuals in order to persist at a tiring but challenging task. Type A and Type B college students completed a Balke treadmill test (at a walking pace) while rating their fatigue at 2-minute intervals. Each subject also completed another treadmill test (at a running pace) that was designed to assess maximum aerobic capacity. Subjects' aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
96
2
3

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(108 citation statements)
references
References 12 publications
7
96
2
3
Order By: Relevance
“…This finding was consistent with those of previous research [4][5][6][7][8][9][10][11], This increased level of physiological arousal in type As relative to type Bs was at variance with the data pertaining to selfreported physical symptoms and state anxi ety. Viewed in the context of their greater HR and SBP change, the lower anxiety and physical symptom report, and particularly the lower heart-racing report by type As, sup ports previous findings of their tendency to underreport physical and emotional symp toms [6][7][8][11][12][13]. However, unlike in Weidner and Matthews' [13] study, under report of symptoms in the present study was not limited to those type As stopped unex pectedly in the middle of a task (i.e.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This finding was consistent with those of previous research [4][5][6][7][8][9][10][11], This increased level of physiological arousal in type As relative to type Bs was at variance with the data pertaining to selfreported physical symptoms and state anxi ety. Viewed in the context of their greater HR and SBP change, the lower anxiety and physical symptom report, and particularly the lower heart-racing report by type As, sup ports previous findings of their tendency to underreport physical and emotional symp toms [6][7][8][11][12][13]. However, unlike in Weidner and Matthews' [13] study, under report of symptoms in the present study was not limited to those type As stopped unex pectedly in the middle of a task (i.e.…”
Section: Discussioncontrasting
confidence: 55%
“…On the one hand, type As have been shown to direct their attention maximally to predesignated tasks of importance, to the detriment of sec ondary tasks given less importance by exper imental instructions [ 14], On the other hand, however, type A individuals have been shown to underreport symptoms of physio logical activation during situations of chal-lengc [e.g. [11][12][13]. The contention arises when the former is used as a direct analogy of the latter [14].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Rate-perceived exertion originated as a construct to describe levels of an individual's perception of physical exertion during exercise. The literature shows that ratings of perceived exertion highly correlate (r = 0.85) with lev els of heart rate during exercise tasks [Skinner et al 1973], Carver et al [1976] have shown that type A males indi cate lower levels of perceived exertion than type B males while working at equivalent levels. However, no studies were found investigating the individual's perception of physical exertion with a concomitant measurement of plasma catecholamines.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental control refers to the tendency of Type A individuals to exhibit aggressiveness and pressured drive in striving to preempt or overcome potentially uncontrollable situations (Krantz, Glass, & Snyder, 1974). Self-control refers to a tendency for Type A individuals to suppress or ignore internal states such as fatigue and emotional distress that signal potential loss of control and may interfere with efforts to master environmental demands (Carver, Coleman, & Glass, 1976).…”
mentioning
confidence: 99%